The relationship between coping styles and professional quality of life among nurses in China with second victim experience / Li Xizhao - Li , Xizhao (2024)
Second-victim experiences can heighten the risk of compassion fatigue, while support from both individuals and organizations tends to serve as a protective factor. However, the potential for poor compassion satisfaction and increased compassion fatigue among nurses, resulting from adverse events, is still an underestimated problem. Additionally, limited knowledge exists regarding the influence of positive and negative coping styles among nurses with second victim experience. Moreover, it is important to recognize that second-victim experiences can have enduring effects on the personal and professional well-being of nurses. Given this, it is crucial to provide individual-centred support to assist nurses in coping with of the second-victim experience. This study aims to examine the impact of second-victim experiences on the professional quality of life among nurses, while also investigating the mediating role of coping styles in the relationship between second-victim experiences and professional quality of life. Furthermore, to explore personal and workplace factors that facilitate or hinder coping styles for second victim experiences, from the perspectives of both frontline nurses and nurse managers. This study was divided into two phases. In phase I, a cross-sectional survey was conducted using a self-administered questionnaire to collect the data consists of demographic data, Second Victim Experience and Support Tool, Simplified Coping Styles Questionnaire, and Professional Quality of Life Scale. Multistage sampling was used to recruit registered nurses from Hunan province in China. There are 899 registered nurses who identified themselves as experiencing adverse events from nine tertiary hospitals were included in this study. Participants were recruited to complete a survey on the second victim experience and support tool, the simplified coping style questionnaire, and the professional quality of life scale. The stress coping theory was used to develop the framework in this study. The structural equation modelling approach was used for conducting the mediating effects analysis via IBM SPSS Statistics 26.0 and Mplus 8.3. In Phase II, Semi-structured interviews were used to collect the data. Purposive sampling was used to recruit 8 nurses and 7 nurse managers from 5 tertiary hospitals located in four cities of varying income levels. The data collected was analysed using thematic analysis in NVivo V.12. In total, 67% (n = 899) of nurses reported a second victim experience during their careers. In a bivariate analysis, both second-victims experiences and coping styles were significantly associated with their professional quality of life. The results showed that the effects of second victim experiences on their professional quality of life were fully mediated by coping styles (95% Bias-corrected bootstrap confidence interval did not contain 0), while the effects varied based on the type of coping styles. The analysis revealed four main themes that influenced nurses’ ability to cope with second victim experiences: “Type of emotional trauma exposure,” “Personal characteristics,” “Workplace environment,” and “Social support system.” This study reveals that secondvictim experiences are prevalent among nurses, necessitating acknowledgment and attention. Disregarding the escalating compassion fatigue and declining compassion satisfaction observed in nurses who have encountered adverse events is both impractical and infeasible. The findings of this study shed light on the mediating effects of coping styles, emphasizing the critical importance of implementing support programs and selfcare initiatives specifically tailored to nurses. Moreover, this study uncovers the facilitators and barriers that nurses encounter while coping with second-victim experiences, providing valuable insights for the development of targeted interventions aimed at supporting nurses' well-being and mitigating the negative consequences of such experiences. Recognizing the significance of a comprehensive approach, it is imperative to implement strategies that effectively support nurses in coping with second-victim experiences, ultimately enhancing patient safety and improving the quality of care delivered.